2021
DOI: 10.18488/journal.ajard.2021.114.262.268
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Farm Performance among Small-Scale Farmers in the Volcanic Highlands of Rwanda: What is the Role of Institutions?

Abstract: This study attempted to examine the role of institutions in boosting rural and agricultural development in the region of the Volcanic Highlands of Rwanda. Both qualitative and quantitative data were collected from a random sample of 401 small-scale farmers through a questionnaire. Data were analyzed using a weighted least-squares method to account for heteroscedasticity, a common issue in cross-sectional studies. Results from crop output function reveal a positive and significant effect of cooperative membersh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 24 publications
0
5
1
Order By: Relevance
“…This is in line with other studies which state that access to microcredit increases agricultural investment in diverse contexts (e.g., Blasé, 1971;Ilebanmi, 1983;Osabohien et al, 2020), with the opposite observed among credit-constrained farmers (Djoumessi et al, 2018;Offor et al, 2021). It, however, contradicts the findings of Maniriho et al (2021), who reported the opposite among small-scale farmers in Rwanda.…”
Section: Access To Microcredit and Effects On Farm Expenditurescontrasting
confidence: 91%
See 1 more Smart Citation
“…This is in line with other studies which state that access to microcredit increases agricultural investment in diverse contexts (e.g., Blasé, 1971;Ilebanmi, 1983;Osabohien et al, 2020), with the opposite observed among credit-constrained farmers (Djoumessi et al, 2018;Offor et al, 2021). It, however, contradicts the findings of Maniriho et al (2021), who reported the opposite among small-scale farmers in Rwanda.…”
Section: Access To Microcredit and Effects On Farm Expenditurescontrasting
confidence: 91%
“…Access to credit has been reported as a key lever for agricultural investment, productivity increases, technology adoption, market participation, and price transmission in many countries across Africa (Alhassan et al, 2020;Osabohien et al, 2020); with its absence impeding agricultural productivity (Assogba et al, 2017;Djoumessi et al, 2018;Mensah et al, 2019;Offor et al, 2021). Few studies have reported negative effects of access to agricultural credit in terms of increased loan delinquency and lower productivity, mainly resulting from unforeseen climate-related risks (e.g., floods and droughts), price volatility, and unstable socio-political environments (Tetteh et al, 2021;Maniriho et al, 2021). Overall, there is a consensus among African academics that the benefits of credit access for agriculture outweigh the costs, especially for smallholder farmers (De Aghon and Murdoch, 2005;Thunstrom, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Experience helps farmers to have a better understanding and a more positive attitude towards farming business development. Maniriho, Musabanganji, and Lebailly (2021) discovered that farmers' experience was a positive and significant factor in yields and incomes. This finding corresponds with Hansen and Jervell (2015), who found that farmers with experience in consistent transformation processes could manage farms effectively, and Haloho, Santoso, Marzuki, Roessali, and Setiadi (2013), who claimed that experience in dairy farming was significantly associated with profit .…”
Section: Factors Affecting the Acceptance Of Dfsmentioning
confidence: 99%
“…Gandasari et al (2021) found that the age of the farmer has a negative effect on performance, as older farmers are less likely to seek new information, are reluctant to adopt innovative practices, and stick to traditional. Furthermore, (Maniriho et al, 2021) suggest that the older the farmer, the less fit they may be to carry out activities, even though they have a wealth of experience. Agyeman et al (2014) found a positive effect of female household head on household income diversification, which contrasted with the findings of Maniriho et al (2021), who found an inverse results, as depicted by a significant differential of farm income between male and female farmers.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, (Maniriho et al, 2021) suggest that the older the farmer, the less fit they may be to carry out activities, even though they have a wealth of experience. Agyeman et al (2014) found a positive effect of female household head on household income diversification, which contrasted with the findings of Maniriho et al (2021), who found an inverse results, as depicted by a significant differential of farm income between male and female farmers. In assessing performance, previous studies have adopted several proxies and measures of performance; this has also resulted in the use of techniques used to analyse the factors which affect performance (Ojo, 2006;Speelman et al, 2008;Verhofstadt and Maertens, 2014;Tajbakhsh and Hassini, 2015).…”
Section: Introductionmentioning
confidence: 99%